Microstructure-refinement–driven enhanced tensile properties of high-pressure die-cast A380 alloy through friction stir processing. (June 2022) - Samanta, Avik; Seffens, Robert J.; Das, Hrishikesh; Guzman, Anthony D.; Roosendaal, Timothy J.; Garcia, David; Song, Miao; Grant, Glenn J.; Jana, Saumyadeep
Abstract: This work employs friction stir processing (FSP), a well-known severe plastic deformation technique, to selectively modify the microstructure of thin-walled, high-pressure die-cast (HPDC) aluminum alloy A380, a major HPDC alloy fabricated in the die casting sector. FSP effectively breaks down Al dendrites and acicular Si particles, creating a homogenized distribution of equiaxed Si particles in the aluminum matrix. After FSP, the refined Si particles ( 1.5 μm) are smaller than the eutectic Si particles (3–8 μm) in HPDC condition. In addition, interparticle distance has decreased almost 50% compared to dendritic arm spacing, and FSP has reduced the aspect ratio of Si particles to 2. Furthermore, FSP eliminates porosity, and breaks down needle-like second-phase Fe-Mn and Cu-rich particles, yielding a refined, homogeneous distribution. The FSP-induced microstructural refinement and porosity reduction improve bulk yield strength and ductility by 23% and 66%. Tensile properties are enhanced beyond those of the die skin of the HPDC plate, and the alloy possesses lower defect density and a highly refined microstructure. This study establishes the viability of FSP as a tool for microstructure modification and mechanical property improvement for HPDC Al alloys for the light-weighting goal of the automotive industries. Graphical abstract: Unlabelled Image Highlights: General purpose high pressure die cast A380 alloy was for the first time subjected to FSP. Ductility of FSP samples is 66% higher than base material with 23% enhancement of yield strength at room temperature. Tensile property enhancement is above those in the skin/die-wall of HPDC material. Combined effect of microstructure refinement and porosity elimination promoted an excellent strength–ductility improvement. FSP-induced large strain caused twinning in Si particles, tangled dislocations in Al grain and precipitation of Cu-rich phase.